Asymmetric Diels-Alder reactions of N-allenoyloxazolidinones catalyzed by Cu(II)-bis(oxazoline) complexes - Torsak Luanphaisarnnont (2018)
© 2014 Elsevier Ltd. All rights reserved. Catalytic asymmetric Diels-Alder reactions of N-allenoyloxazolidinones were investigated. Various chiral metal-bis(oxazoline) and metal-pyridinebis(oxazoline) complexes were screened. Cu(SbF6)2(H2O)2(t-BuBox) was found to be the most effective catalyst, giving the product in high yield, enantioselectivity, and endo:exo selectivity. The relative reactivity between N-allenoyloxazolidinones and N-alkenoyloxazolidinones was also investigated. A model for stereoinduction was proposed to account for the enantioselectivity and endo:exo selectivity.